Uma análise hierárquica dos comportamentos de engajamento do consumidor com a marca nos sites de redes sociais - Nery, Maria Martins Rebouças (2021)
Consumer brand engagement (CBE) on social networking sites (SNS) presents itself as a new insight into the relationships established in these environments as it is able to reflect the intensity of consumers' connection with the brand and their propensity to participate in brand-related activities. In order to provide content that engages consumers, managers need to understand the psychological and motivational characteristics that lead them to interact with the brand, since these individual characteristics present themselves as a guiding factor for CBE in SNS practices. Based on the Metatheoretical Model of Motivation and Personality (3M Model), which is structured in an integrated four-level system, a hierarchical model is developed that explains how the individual's elementary traits of personality relate to traits at the intermediate levels, called composite traits - understood from their information and socialization needs - and situational traits - which comprise the consumer's psychological engagement with the brand - to explain the performance of engagement behaviors in SNS. The aim is to identify how elemental, composite, and situational personality traits combine to influence brand engagement behaviors in these environments. To this end, a quantitative approach is used with data collected through a survey. Direct relationships between traits from the most abstract level to the higher level are analyzed using partial least squares structural equation modeling (PLS-SEM), and indirect relationships that test the role of intermediate traits in the relationships between the more abstract and concrete levels of the model are analyzed using the PROCESS macro. The results point out that there is indeed a hierarchical relationship between personality traits and engagement behaviors and that consumers’ psychological brand engagement plays an important mediating role in these relationships. The findings contribute to the understanding of the psychological mechanisms that lead consumers to perform brand engagement activities on social networks, contributing theoretically and practically to the study of CBE in SNS and opening a number of opportunities for further research on the topic.